Estudio de la vaporización de elementos traza durante la combustión de barros cloacales - Flamant, Gilles (2010)
The behavior of 11 trace elements during the sewage sludge combustion and its co-combustion with municipal solid wastes was thermodynamically investigated in order to observe the influence of different operating parameters. The thermodynamic calculations were carried out simulating the existing atmosphere during the sewage sludge combustion, between 200 and 1000 C, working at atmospheric pressure. Also, the contents of chlorine and sulphur in this atmosphere was analyzed, because these elements can exist during the co-combustion with municipal solid waste. Experimentally, the sewage sludge combustion in fluidized bed was carried out. The study was focalized in three representative toxic metals: Cd, Pb, Zn. The results show that the co-combustion with municipal solid wastes makes it difficult trace elements vaporization, since metallic chlorides react with water forming oxides which remain in the mineral matrix. The experimental study confirmed the important dependence of the heavy metals vaporization upon the operating parameters.